ANALISIS PENGARUH PENDIDIKAN, PELATIHAN, DAN PENGALAMAN KERJA TERHADAP PRODUKTIVITAS KERJA PEGAWAI DINAS PERTAMBANGAN DAN ENERGI PROVINSI PAPUA - Melmambessy Moses (Universitas Trisakti, 2012)
The purpose of this study is to test and analysis the effects of education, training and work experience to work productivity. The sample is the employees of Dinas Pertambangan and Energy Papua. Statistik integral model of multiples regression analysis is used to analyze the data. The result showed that (1) the effects of education, training and work experience to work productivity are significant, (2) the effects of education to work productivity bigger than training and work experience training and work experience.Keywords : Education, Training, Work experience, Work productivity